Study of soil water-erosion intensity and vegetation cover of an oak-spruce forest in the Pokutsko-Bukovina Carpathians, Ukraine - Blinkova, Olena; Lavrov, Vitaliy (Archives of Biological Sciences, 2017)
The effect of soil erosion on dynamic changes in vegetation cover is an important subject of regional ecological research of the Ukrainian Carpathians. Studies on soil erosion on the Pokutsko-Bukovina Carpathians have focused on the impact of soil water erosion on tree, shrub and herbaceous layers in intensive, moderate, slight and light erosion zones. Results have shown that the intensity of water erosion and runoff, which depend on slope steepness, have a great impact on changes in the vegetation cover. This paper compares the main morphometric parameters of formed ravines, the health and composition of trees, and the composition of the herbaceous layer. The floristic list of the all experimental plots comprised 61 grass species. The stands formed Quercus robur L. and Abies alba L. Assessment of the functional types of plant species showed that the balance between competition, stress and disturbance is disrupted along a gradient of water-erosion soil transformation. Soil erosion is likely to have caused a change in the edaphic matrix. The distribution of life forms is also disturbed. Analysis of species richness of the vegetation cover under water erosion and the prevailing soil conditions showed that the values of indices depend on erosion intensity. https://doi.org/10.2298/ABS161206008B Received: December 6, 2016; Revised: January 30, 2017; Accepted: February 17, 2017; Published online: March 10, 2017 How to cite this article: Blinkova O, Lavrov V. Study of soil water-erosion intensity and vegetation cover of an oak-spruce forest in the Pokutsko-Bukovina Carpathians, Ukraine. Arch Biol Sci. 2017;69(4):627-36.